INNER AND OUTER WO RLDS: ON THE NATURE OF THINGS, MATTER, AND THE MIND IN THE GŌNGSŪN LÓNGZǏ - Indraccolo, Lisa (Problemos, 2016)
The present study provides an overview of the narrative of cognition as described in a largely understudied Classical Chinese philosophical text, the Gōngsūn Longzi, drawing meaningful comparisons with other works traditionally associated with the Logicians’ (mingjiā) trend of thought. The Gōngsūn Longz especially provides a substantial contribution to our understanding of knowledge construction processes in early China. According to the text, the mind has the ability to operate distinctions. It breaks reality down into meaningful, manageable units, and classifies these units according to appropriate categories. As will be shown, such ability is not only necessary for the individual to cognize the world, but also sufficient to ensure univocal correspondence between names and actualities.
Keywords: Early China; Logicians; Gōngsūn Longz; cognitive categories; percepts